GEOSTATISTICAL TEST USING LEAST SQUARE ADJUSTMENT COMPUTATION TO OBTAIN THE REDUCTION PARAMETER FOR DSM TO DEM CONVERSION (Study of Case: Cilacap, Indonesia) - Atriyon Julzarika (BRIN, 2010)
Abstract. ALOS satellite is one of the natural resources satellites that can be used for 3Dmodel applications. The problems of 3D model generation based on satellite imagery arethe model always in Digital Surface Model (DSM), not in Digital Elevation Model (DEM).The reference system of 3D model that are produced by ALOS satellite image is still assurface for z axis, whereas x axis and y axis has been closed to 2D reference system insome certain datum and system of map projection. Therefore, it needs a research to observethe accuracy and the precision of ALOS satellite data using a least square adjustment inparameter methods. The results of this research will be used as a reference for next researchto find a way for changing DSM from ALOS satellite image to be DEM automatically.